Infiltrative multifocal glioblastoma progression in a twelve-year-old boy after COVID-19 infection: a case report - Angky Saputra; Zaky Bajamal; Francisca Notopuro; Lucia Dwi Puspitasari (DiscoverSys Inc., 2022)
Background: Glioblastoma is one of the most malignant types of primary central nervous system tumors with a high recurrence rate and dismal prognosis. Multifocal glioblastoma has been shown to have a poorer prognosis than solitary glioblastoma. Cancer patients are at risk of contracting COVID-19. It is hypothesized that COVID-19 may induce glioma tumorigenesis via angiotensin enzyme 2 receptor. We reported a rare pediatric multifocal glioblastoma in a twelve-year-old boy complicated with COVID-19. Case Presentation: The patient was a twelve-year-old boy with a new-onset unprovoked seizure and headache. Magnetic resonance imaging (MRI) showed a heterogeneous solid cystic mass in the left temporal region (2.1x2.1x2.8 cm) with an increased choline/creatinine ratio and choline/n-acetyl acetate aspartate (NAA) ratio suggestive for high-grade glioma. The patient was contracting COVID-19 shortly after the diagnosis of glioblastoma. Two weeks later, patients came with significant neurological deterioration, hemiparesis, headache, and vomiting. MRI showed an infiltrative mass in the temporal and parietal region (5.05x8.03x8.3 cm) with intratumoral hemorrhage, also causing midline shift deviation (11.9 mm). The patient underwent trepanation and total safe resection of the tumor. Histopathological findings showed neoplastic cells with abundant mitotic figures, necrotic foci and pseudopalisading necrosis. These findings confirmed the diagnosis of multifocal glioblastoma. Conclusion: Glioblastoma is a rare disease in the pediatric population with a poor prognosis due to its infiltrative nature and high recurrence rate. The patient had an acute deterioration of the neurological condition and rapid growth of the tumor after he contracted COVID-19, which may or may not be incidental. Further observation of similar cases will be required to determine the association between glioblastoma and COVID-19.